Diseño de propuesta administrativa y operativa para el área de alimentos y bebidas del Gran Hotel San Francisco, provincia del Carchi, Ecuador - León Pulla, Juan Francisco (2020)
The purpose of this study is to formulate a proposal to reactivate the food and beverage department in the restaurant belonging to the Hotel San Francisco in the city of San Gabriel. Regarding the state of the art, previous studies such as those by Silva (2015), Castellano and Badillo (2015), Correia (2012) and Reinoso (2011) were reviewed. Theoretically, the study is based on the functioning of a hotel's food and beverage department: definition, importance, organizational and operational structure, marketing strategies, and documentation required to support operations. This also includes matters relating to establishing the current state of demand and supply of the food and beverage service within the San Francisco hotel and strategies for its strengthening. It is a descriptive study, non experimental, data were collected from primary sources through direct observation, interview and survey techniques. The results showed that the restaurant's offer has been reduced to breakfasts, although the facilities of the food and beverage department within the Hotel San Francisco are equipped for a full service. The strategic weakness of developing a plan and not disseminating it among the personnel involved was proven. The need to support the administrative processes was also established by giving it formality through the description of positions and the creation of the administrative structure, as well as the need to develop the marketing strategy that best suits the hotel. The findings made it possible to develop the proposal based on a strategic plan, made up of the administrative aspects that refer to the philosophical foundations of management, the organizational structure, functions and positions, as well as the documentation that supports the operations together with the standardization of the recipe book\; all aimed at improving the performance of the food department. As a complement, the marketing strategy was developed that includes image renewal, uniforms, menu and advertising on social networks.